Women's Experiences of Embodied Identity through Active Leisure. (3rd March 2020) - Mayoh, Joanne; Jones, Ian; Prince, Sam
ABSTRACT: This article contributes to the small yet emerging body of literature that provides an analysis of active leisure to propose how it may provide existential possibilities for empowerment and the wellbeing for women. We have specifically explored women's experiences since it is broadly accepted that we experience our bodies in gendered ways. In this article, which combines theoretical discussion and qualitative empirical data from in-depth interviews with a female power lifter, we draw upon phenomenologically informed dwelling-mobility theory to explore examples of how active leisure provides these opportunities for wellbeing through the experiential lifeworld dimensions of embodiment and identity. Our discussion demonstrates that active leisure provides a pathway for women to have more empowering body experiences by developing an embodied identity that provides a sense of "I am my body" or "my body can."